Impact of oil droplet concentration on the optical, rheological, and stability characteristics of O/W emulsions stabilized with plant-based surfactant: Potential application as non-dairy creamers. (March 2018) - Chung, Cheryl; Sher, Alexander; Rousset, Philippe; McClements, David Julian
Abstract: The development of plant-based foods and beverages is becoming increasingly popular because of growing consumer concerns about perceived ethical, health, and environmental issues. The current study examined the influence of oil droplet concentration on the physicochemical properties of oil-in-water (O/W) emulsions stabilized with a plant-based surfactant. Emulsions were utilized as model creamers, which consisted of medium chain triglycerides (MCT) as the oil phase and quillaja saponin as a plant-based surfactant. The optical, rheological and stability properties of these model creamers were measured at varied oil content from 0 to 15%, at a constant surfactant-to-oil ratio (1:15). The model creamers had an appearance similar to that of commercial non-dairy creamers, and their whiteness increased with increasing droplet concentration due to enhanced light scattering: L* from 77 to 91 for creamer and L* from 5 to 55 for white coffee. The quillaja saponin-coated lipid droplets were stable to aggregation and gravitational separation when added to hot acidic coffee solutions (85°C, pH 4.9), which was attributed to strong steric and electrostatic repulsions. The apparent viscosity of the model creamers increased with increasing droplet concentration due to increased frictional losses associated with the presence of the droplets. This study provides valuable information into the impact of oil content on the physicochemical properties of liquid creamers using plant based surfactants, which is important for the formulation of healthier products. Graphical abstract: Schematic diagram of light scattering patterns in different emulsions with different droplet concentrations (0–15%). As the droplet concentration increases there is more multiple scattering and overlap of the polarization fields. Highlights: Plant-extracted quillaja saponin was utilized as surfactant to prepare non-dairy model coffee creamers. Quillaja saponin stabilized model creamers had milk-like appearance similar to commercial creamer. Increasing oil content increased lightness of model creamers due to enhanced light scattering and able to whiten coffee. The model creamers added to coffee solutions were stable to aggregation due to strong steric and electrostatic repulsions.